Squirrel-Seed Interactions: The Evolutionary Strategies and Impact of Squirrels as Both Seed Predators and Seed Dispersers - Steele, Michael A.; Yi, Xianfeng (Frontiers in Ecology and Evolution, 2020)
For many squirrel species, their intense—arguably coevolutionary— interactions with seed and nut producing trees have significantly shaped their biology and diversity.  Here we provide an overview of this relationship in a range of forest types worldwide. We first review the evidence for how forest composition (conifer, hardwood, mixed hardwood and overall diversity of tree species) influences interactions between squirrels and seed trees and, ultimately, the role of squirrels as either seed predators or seed dispersers. We review, for example, the intense selective pressure squirrels exert on conifer trees as seed predators and the diversity of morphological traits and behavioral strategies that allow them to efficiently exploit this critical resource.  In contrast, we show how the squirrel's role shifts to one of seed disperser in hardwood forests and how the specifics of this interaction varies further with forest structure, forest composition and climactic conditions. We then review the growing evidence for the tight ecological and evolutionary dance between the squirrels and the oaks that has shaped the biology of both across the globe.  We show how a suite of seed (acorn) characteristics (e.g., chemical gradients, germination schedules, seedling morphology and tolerance-resistance strategies) are all intimately tied to the scatter-hoarding decisions of several squirrel species. And, based on studies in oak forests in Central America, Mexico, North America, and Eurasia–many by the authors–we also highlight the behavioral strategy of embryo excision now reported for six species across at least four genera of squirrels. This behavior, glaringly absent in other scatter-hoarding rodents worldwide, is now known be an innate trait in at least two species, one in Asia and another in North America. We review extensive recent research on one species of squirrel, the Siberian chipmunk (Tamias sibiricus), which exhibits a suite of behavioral strategies unique to that of other squirrels that independently contributes to seed dispersal and establishment. Finally, we outline numerous remaining questions concerning plants and other taxa of squirrels still open to investigation.